Elaboración de un fertilizante natural a base del tallo de banano (Musa Paradisiaca.L.) - Córdova Oviedo, Damarys Nagelly (2026)
Banana cultivation is one of Ecuador's main economic activities, as it generates employment. However, these agricultural activities have an environmental impact at harvest time due to organic waste such as pseudostems, leaves, and stems. In the case of the Riobamba wholesale market, between 8 and 10 tons of waste are generated daily, 90% of which is organic, including banana stems. Considering the high volume of waste that is generated, the present study proposes adding value to this by-product through the production of a natural fertilizer made from banana stems, which were collected at the market. The methodology employed was quantitative and experimental. It is important to emphasize that the fertilizer produced is a solid product containing other naturally derived components. Two dehydration methods, tray dehydration and solar dehydration, were applied to the banana stems to determine which of the two methods is the most suitable for dehydrating the banana stems; that is, to test whether essential nutrients such as nitrogen, potassium, and phosphorus are maintained or vary during the dehydration process. After obtaining the physicochemical results, including N, P, K, pH, moisture, ash content, C/N ratio, and organic matter (OM) for both types of stems, the tray-drying method was selected for further work. This decision was based on its optimal C/N ratio, its high organic matter content, and its adequate concentrations of nitrogen, phosphorus, and potassium. Subsequently, a control treatment without banana stems was established; it included organic materials such as cattle manure, wood ash, and coffee grounds. These materials were used as components for the three treatments containing banana stems in different percentages. The treatments were formulated in this manner to evaluate how the percentage of NPK (nitrogen, phosphorus, and potassium) varied. For the statistical analysis, the NPK values of each treatment were measured in triplicate. An ANOVA was applied to determine significant differences among the treatments, identifying the treatment with the most favourable values for producing the natural fertilizer from banana stems. The economic feasibility of the fertilizer was analysed by considering production costs, labour, and operating expenses, as well as estimating the selling price (SP) and benefit–cost ratio (B/C).